Aggression, DRD1 polymorphism, and lesion location in penetrating traumatic brain injury. (11th March 2014) - Pardini, Matteo; Krueger, Frank; Hodgkinson, Colin A.; Raymont, Vanessa; Strenziok, Maren; Amore, Mario; Wassermann, Eric M.; Goldman, David; Grafman, Jordan H.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective This study evaluated whether structural brain lesions modulate the relationship between pathological aggression and the dopaminergic system in traumatic brain injury (TBI). While converging evidence suggests that different areas of the prefrontal cortex modulate dopaminergic activity, to date no evidence exists of a modulation of endogenous dopaminergic tone by lesion localization in penetrating TBI (pTBI). Methods This study included 141 male Caucasian veterans who suffered penetrating pTBI during their service in Vietnam and 29 healthy male Caucasian Vietnam veterans. Participants were genotyped for 3 functional single nucleotide polymorphisms (SNPs): dopamine receptor D1 (DRD1) rs686, dopamine receptor D2 (DRD2) rs4648317, and catechol-O-methyltransferase (COMT) Val158Met. Patients underwent brain CT scans and were divided into medial prefrontal cortex, lateral prefrontal cortex, and posterior cortex lesion groups. Long-term aggression levels were evaluated with the agitation/aggression subscale of the Neuropsychiatric Inventory. Results Our data showed that carriers of more transcriptionally active DRD1 alleles compared to noncarriers demonstrated greater aggression levels due to medial prefrontal cortex lesions but reduced aggression levels due to lateral prefrontal cortex lesions independently of DRD2 rs4648317 or COMT Val158Met genotypes. Conclusions Our results suggest that the relationship between pTBI-related aggression and the dopaminergic system is modulated by lesion location. Potentially lesion location could represent an easy-to-use, widely available, para-clinical marker to help in the development of an individualized therapeutic approach to pTBI-related pathological aggression.